AYURVEDA TREATMENT PROTOCOL IN FEMALE INFERTILITY DUE TO PCOS & HYPOTHYROIDISM (International Journal of Ayurveda and Pharma Research, 2021)
Infertility is a global problem in one among six couples who wishes to conceive. In Ayurveda Infertility is termed as ‘Vandyatwa’ and is explained in detail. Polycystic Ovarian Syndrome (PCOS) is becoming very common in females of reproductive age and Ovulatory Dysfuction due to PCOS is one of the main reasons for female infertility. The factor for a healthy conception, pregnancy and delivery is mentioned as “Garbha Sambhava Samagri” (factors essential for conception). Acarya Susruta explained it as Rtu (ovulation), Ksetra (healthy uterus and associated structures), Ambu (proper nourishment) and Beeja (healthy sperm & ovum). Sukla (sperm) & Arthava (ovum) are considered as “Anthima Dhatus” (final tissues) therefore proper metabolism is essential for the formation of healthy ovum and sperm. Considering the present case the patient had the history of hypothyroidism and bilateral PCOS, both results in improper metabolism which further results in inadequate development of follicles and anovulatory cycles leading to infertility. In this case evidences of defective Dhathuparinama (process of tissue formation) can be visualized like irregular cycles, Thin Endometrium, Infertility and Increased blood sugar level. Ayurveda treatment including Sodhana (purificatory therapies) and Samana (pacification treatments) is adopted to regularise her cycles, improve the quality of ovum, to reduce the blood sugar level and thereby enhancing the chance of conception. After our treatment the patient conceived soon and now, she completed 28 weeks successfully.